The landscape of rare mitochondrial DNA variants in sudden cardiac death: A potential role for ATP synthase - Elena Luppi; Monica De Luise; Carla Bini; Guido Pelletti; Gaia Tioli; Ivana Kurelac; Luisa Iommarini; Susi Pelotti; Giuseppe Gasparre (Heliyon)
Sudden cardiac death (SCD) is a major health concern, which can be the sign of a latent mitochondrial disease. However, mitochondrial DNA (mtDNA) contribution is largely unexplored in SCD at population level. Recently, mtDNA variants have been associated with congenital cardiopathy and higher risk of ischemic heart disease, suggesting them as potential risk factors also in SCD. Therefore, we aimed to define the mtDNA mutational landscape in such phenotype, by sequencing the whole blood mtDNA genome in a pilot cohort of 28 unrelated subjects. Coding variants were prioritized according to their population and haplogroup frequency. Out of 28 patients, 36% were diagnosed with coronary artery disease, 39% with structural defects and 25% with unspecified cardiac disease. The overall frequency of macro-haplogroups followed the distribution in the European population. No known or novel mtDNA pathogenic variants were found. Two rRNA and 8 missense variants were rarer than polymorphisms as they had a frequency lower than 1% in population databases. 5/8 missense variants clustered in ATP synthase genes and 4/8 missense variants were previously detected in patients with suspected mitochondriopathy. We concluded that primary mitochondrial disease is not a major cause of SCD, but rare mtDNA variants may occur (35.7% in our cohort vs 0.65% in the population; p < 0.01), potentially modifying the risk.